PARANEOPLASTIC SENSORY NEUROPATHY: REPORT OF 6 CASES - A CHIT SAZ (Journal of Research in Medical Sciences, 2002)
Sometimes before signs of lung tumor, peripheral nerve involvement with sensory neuropathy tell us about lung cancer. This sensory neuropathy often accompany with oat cell carcinoma of lung. The initial symptoms are numbness or paresthesic in a limb and over a period of days or weeks symptoms became bilateral and spread to trunk. Areflexia and autonomic dysfunction as cardiac arrhythmia, gastric atonia, illeus and orthostatic hypotension accured. In CSF there is pleocytic Iyphmphocytes. Electra diagnostic test (NCV) compatible with loss of sensory potentials. In this survey in Alzahra hospitol (1999-2000) affiliated to IUMSHS, 64 patients with neuropathy, were investigated. Chest x-ray and lung CT scan was prepared for them. Bronchoscopy and biopsy of lung was done in indicated ones. On the other hand electrodiagnostic (NCV) and cerebrospinal fluid (CSF) study were done in then. Among 64 patients with neuropathy, six patients had lung tumors with sensory neuropathy. The commonest sign of diseas was limb paresthesia. In 84 percent of patients, tendon reflex in lower limbs was absent. The commonest tumor was out cell carcinoma of lung and 15 percent of patients had muscle pain in early phase of disease. CSF showed pleocytose of Iymphocytes. NCV showed absent of sensory potentials in 100 percent of patients.